2017
DOI: 10.1136/bmjopen-2017-017218
|View full text |Cite
|
Sign up to set email alerts
|

DetectaWeb Project: study protocol of a web-based detection of mental health of children and adolescents

Abstract: IntroductionTraditionally, research and practice addressing mental health has been conducted within a unidimensional model, explaining mental health as the presence/absence of psychological problems (distress or psychopathological symptoms). More recently, accumulative evidence has supported a bi-dimensional model, which conceptualises psychological problems and psychological strengths (well-being) as related-yet-distinct continua that, when considered together, yields a more comprehensive understanding of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…The SDQ uses a three-option response format (0 = not true, 1 = somewhat true, 2 = certainly true). The internal consistency for this study's sample was similar to those reported in previous studies [11,35,36]. In S2, Omega hierarchical was 0.73 for externalizing symptoms, 0.80 for internalizing symptoms, 0.78 for prosocial behavior, and 0.80 for the total score.…”
Section: Brief Mental Health Measuressupporting
confidence: 86%
See 2 more Smart Citations
“…The SDQ uses a three-option response format (0 = not true, 1 = somewhat true, 2 = certainly true). The internal consistency for this study's sample was similar to those reported in previous studies [11,35,36]. In S2, Omega hierarchical was 0.73 for externalizing symptoms, 0.80 for internalizing symptoms, 0.78 for prosocial behavior, and 0.80 for the total score.…”
Section: Brief Mental Health Measuressupporting
confidence: 86%
“…The survey instrument was administered online to students schoolwide within a universal prevention framework [11]. In the present study, we used the web-based assessment protocol for BMHM of children and adolescents, the DetectaWeb Project (for further details, see its description in Piqueras et al) [11]. The convenience sample of recruited students were organized within their respective centers in order to complete the questionnaire in their schools' computer rooms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study falls within the framework of a broader research on mental health in adolescents (2016/2017) (DPS-JPR-004–16) [37], where 909 students between the ages of 12 and 18 years from the province of Alicante formed an initial sample at time 1 (t1). The second time of assessment was made six months later (t2) and consisted of 238 adolescents.…”
Section: Methodsmentioning
confidence: 99%
“…This protocol aims to self-assess personal resources to cope with the psychological impact of the current health crisis. The survey was carried out using the online data collection platform DetectaWeb (Piqueras et al, 2017). Participants completed the survey online and, at the end, received a report with their personalized results along with recommendations and suggestions for the improvement of personal resources and the reduction of the health crisis's impact.…”
Section: 1study Designmentioning
confidence: 99%